الحماية القانونية للحقوق المالية لطفل في التشريع الجزائري - بوساحة, نجاة (University of Eloued جامعة الوادي, 2021)
عني المشرع الجزائري بفئة الأطفال القصر من جميع النواحي ،خاصة ما تعلق بذمة الطفل المالية، وذلك من خلال إضفاء حماية قانونية على أمواله، التي تتنوع مصادرها بين الوقائع القانونية المتمثلة في حقه في النفقة التي يثبت له لأنه ينتمي لأسرة معينة ،وكذا حقه في الميراث في حال وفاة أحد مورثيه، كما قد يكون مصدر أمواله تصرفات قانونية لصالحة عقد الهبة أو الوصية، هذا من جهة. ومن جهة أخرى ولضمان حماية هذه الأموال نظم المشرع ما يعرف بأحكام النيابة الشرعية، والتي من خلالها يمكن لولي الطفل القاصر أو وصيه أو قيمه حسب الحالة إدارة أمواله والحفاظ عليها واستثمارها، ولضمان ذلك أضفى المشرع رقابة قضائية على تصرفات النائب الشرعي. The Algerian legislator has always been concerned with the category of minor children in all aspects, especially whatis related to child patrimony. In one hand, by providing legal protection over his property whose sources differ in legal facts namely his right to maintenance proven as he belongs to a certain family, his right in inheritance in case one of the legators died, and it may be legal transactions for him like donation or will contract. On the other hand, in order to protect those properties,the legislator regulated what is known by legal proxy, through which the person having custody of the minor child, his trustee, or his guardian can administer, save and investthem. To ensure this, the legislator brought judicial control over the legal prosecutor's actions
مقال
Keywords: الطفل القاصر ; الحق ; المالي ; النائب ; الشرعي ; رقابة ; القضاء